Pemberdayaan peternak kambing Dukuhmencek melalui pendekatan pentahelix untuk mendukung ketahanan pangan lokal: Empowerment of goat farmers in Dukuhmencek through a pentahelix approach to support local food security - Endang Suprihati; Andi Estetiono; Miyayu Soneta Sofyan; Tika Widiastuti; Eka Puspa Dewi; Nizar Hosfaikoni Hadi; Pandu Dwi Prasetyo; Muhammad S. A. Priyanata; Mohammad F. Q Akbar (IGKOJEI: Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT  The sheep farming subsector plays a strategic role in supporting national food security but continues to face challenges related to productivity, animal health, and waste management. This article documents a community engagement program based on the pentahelix model implemented in Dukuhmencek Village, Jember Municipality, which aims to enhance sheep farmers' capacity through the synergy of academia, community, government, social institutions, and business actors. The program was conducted from June to August 2025 through a series of training and mentoring activities covering forage and silage production, animal health, farm management, the development of Standard Operating Procedures (SOPs), and the utilisation of livestock waste into bio-organic fertiliser. The method employed was a participatory approach involving interactive training, hands-on practice, and evaluation through pre- and post-tests. The evaluation results indicate significant improvements in knowledge, including silage (58.3%), animal health and farm management (38.3%), SOP development (47.9%), and bio-organic fertiliser (32.9%). Furthermore, farmers successfully practised technical skills such as vitamin injection, deworming, and the production of environmentally friendly organic fertiliser. The program has contributed to strengthening farmers’ professionalism, reducing environmental impacts, and diversifying income sources. These findings highlight that the pentahelix approach is not only relevant for enhancing individual capacity but also effective in strengthening sustainable livestock ecosystems at the village level.  Keywords: Bio-organic; Community empowerment; Food security; Pentahelix; Sheep farming      ABSTRAK  Subsektor peternakan kambing memiliki peran strategis dalam mendukung ketahanan pangan nasional, namun masih menghadapi kendala produktivitas, kesehatan ternak, dan pengelolaan limbah. Artikel ini mendokumentasikan program pengabdian masyarakat berbasis model pentahelix yang dilaksanakan di Desa Dukuhmencek, Kabupaten Jember, dengan tujuan meningkatkan kapasitas peternak kambing melalui sinergi akademisi, masyararakat, pemerintah, yayasan sosial, dan pebisnis. Dalam rangka mencapai ketahanan pangan, dilakukan serangkaian pelatihan dan pendampingan mencakup pengolahan pakan (hijauan dan silase), kesehatan ternak, manajemen kandang, penyusunan Standar Operasional Prosedur (SOP), serta pemanfaatan limbah menjadi pupuk bio-organik. Metode yang digunakan adalah pendekatan partisipatif melalui pelatihan interaktif, praktik lapangan, serta evaluasi pre-test dan post-test. Hasil evaluasi menunjukkan peningkatan signifikan pada aspek pengetahuan, antara lain silase (58,3%), kesehatan ternak dan manajemen kandang (38,3%), SOP (47,9%), dan pupuk bio-organik (32,9%). Selain itu, peternak mampu menguasai keterampilan teknis seperti penyuntikan vitamin, pemberian obat cacing, serta produksi pupuk organik ramah lingkungan. Program ini berimplikasi pada penguatan profesionalisme peternak, pengurangan dampak lingkungan, serta diversifikasi sumber pendapatan. Temuan ini menegaskan bahwa pendekatan pentahelix tidak hanya relevan dalam meningkatkan kapasitas individu, tetapi juga efektif memperkuat ekosistem peternakan berkelanjutan di tingkat desa. Kata kunci: Bio-organik; Ketahanan pangan; Pengabdian masyarakat; Pentahelix; Peternakan kambing.